2021
DOI: 10.15244/pjoes/137329
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Trace Elements in Raptors from Three Regions of Slovakia, Central Europe

Abstract: Slovakia situated in the territory of Central Europe has a rich mining and industrial history with a strong pollutive impact on the environment, with heavy metals and metalloids as the most often analysed pollutants. Despite a relatively advanced toxic elements research, none enquiry has been performed in birds of prey, the most suitable bioindicators, in Slovakia yet. Regarding the lack of information, the presented study represents the first integrated results of the contamination status of raptor species wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…S2 ), the difference was not confirmed by the GLM analysis ( Χ 2 = 1.21, p = 0.27). The levels we found in the eagles were comparable to those recently reported in other raptors from Slovakia (Hurníková et al 2021 ) but tens of times lower than those found in previous decades in white-tailed eagles from the Baltic coast (Fig. 5 ).…”
Section: Resultssupporting
confidence: 91%
“…S2 ), the difference was not confirmed by the GLM analysis ( Χ 2 = 1.21, p = 0.27). The levels we found in the eagles were comparable to those recently reported in other raptors from Slovakia (Hurníková et al 2021 ) but tens of times lower than those found in previous decades in white-tailed eagles from the Baltic coast (Fig. 5 ).…”
Section: Resultssupporting
confidence: 91%
“…Considering Cd, its toxicity on wildlife due to nephrotoxicity, carcinogenicity, anaemia, or interaction with the metabolism of calcium and other essential elements is well-documented and may also lead to disturbance in reproduction (Eisler 1985). The main driver of exposure of wildlife to Cd is the degree of contamination of their habitats (Hurníková et al 2021). If its breeding habitat is mainly associated to the open woodland, the Réunion harrier forages in diversi ed habitats including agricultural areas (Bretagnolle et al 2000) that have been shown to be contaminated by Cd due to the use of mineral fertilizers in the Réunion island (Doelsch et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Guizhou Province had the largest blueberry planting area and output in China at the end of 2020 [1], with blueberries becoming one of the main agricultural products driving the local economy. The soil environment is the foundation of agricultural development, and environmental health is inextricably linked to agricultural product quality and safety [2,4]. Soil, as the growth environment of crops, has a considerable impact on the heavy metal content of crops [5,6].…”
Section: Introductionmentioning
confidence: 99%